Autocorrelation of spatial allocation of funds at the municipality level of Slaskie Voivodship - Marcin Niemiec; Anna Szelag-Sikora; Jakub Sikora; Michal Cupial; Joanna Rorat (Institute of Economic Research (IER), 2017)
Research background: Local development is a harmonized and systematic activity of the local community, local authorities and other entities operating in a municipality, aimed at creating and improving the usability of existing municipalities. The primary factor in the local development is investments undertaken by the municipality. The financial reflection of these activities is the amount of investment expenditure. The amount of a municipality's income, its development strategy and the expectations of the local communities influence both the level of investment expenditure and structure, which is diversified both in terms of time and space. Purpose of the article: The aim of the study was to determine the spatial distribution of total funds allocated for investment, and investments in transport and communications in the municipalities of Slaskie Voivodship. Spatial relationship was also determined with the Moran's I statistic. The scope of work included creating a spatial database of the examined region at the level of basic local government units, i.e. 167 municipalities. The data were obtained from the studies of official statistics for the years 2008, 2011 and 2014. Methodology/methods: Based on information contained in attribute data sheets, along with the postal codes of municipalities, a spatial database was created in the program ArcView. The analyzed maps were prepared in the GIS program ArcView. For better illustration and reading of detailed data from the prepared maps, the attribute variables were divided into groups using the Jenks method. With it, classes could be determined by comparing the sum of the squares of the differences. The developed classes can also be called a natural border of the division. Based on the prepared spatial database, an analysis was performed with the program R-cran, using Moran's I statistics. Moran's I statistic determines the differences and similarities between the two objects, and allows analyzing the researched area.Findings: With relation to the analysis of the total funds allocated for investment, the least among the investment periods studied was the year 2008. Noticeable in this period is the largest number of municipalities included in class I (142 municipalities), with the investment range 0 - 6,510,016.26 zloty. The developed spatial distribution shows that municipalities concentrated in the central part of the voivodship make up an island of high investment funds. These communes are located in the Upper Silesia Agglomeration, with a high population density. High values are also noticeable in large urban centers such as Czestochowa in the north of the voivodship, and Bielsko-Biala in the south.
Keywords: C19; H76; R12; 330; investment funds; municipality; spatial autocorrelation; GIS; Moran's I statistics